2014
DOI: 10.1371/journal.pone.0098477
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of Developmental Processes and Defense Signaling by Growth Regulating Transcription Factors

Abstract: Growth regulating factors (GRFs) are a conserved class of transcription factor in seed plants. GRFs are involved in various aspects of tissue differentiation and organ development. The implication of GRFs in biotic stress response has also been recently reported, suggesting a role of these transcription factors in coordinating the interaction between developmental processes and defense dynamics. However, the molecular mechanisms by which GRFs mediate the overlaps between defense signaling and developmental pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 87 publications
(113 reference statements)
1
56
0
Order By: Relevance
“…This implies that an altered steady state has been reached in the cytokinin signaling pathway in 35S:GRF5 and grf5-1 plants, which could explain the increased sensitivity of 35S:GRF5 plants to cytokinin-driven stimulation of cell division and leaf longevity. Recently, analysis of the root transcript profiles of the grf1 grf2 grf3 triple mutant and plants overexpressing rGRF1 or rGRF3 revealed a significant overlap with a robust set of cytokinin-responsive genes, defined as the golden list, including ARR9 (Bhargava et al, 2013;Liu et al, 2014b). Moreover, GRF1 and GRF3 transcript levels were reduced in 2-week-old ahk2 ahk3 double mutant plants, corroborating that GRFs and cytokinins interact (Liu et al, 2014b).…”
Section: Grf5 and Cytokinins As Coordinators Of Chloroplast Division mentioning
confidence: 85%
“…This implies that an altered steady state has been reached in the cytokinin signaling pathway in 35S:GRF5 and grf5-1 plants, which could explain the increased sensitivity of 35S:GRF5 plants to cytokinin-driven stimulation of cell division and leaf longevity. Recently, analysis of the root transcript profiles of the grf1 grf2 grf3 triple mutant and plants overexpressing rGRF1 or rGRF3 revealed a significant overlap with a robust set of cytokinin-responsive genes, defined as the golden list, including ARR9 (Bhargava et al, 2013;Liu et al, 2014b). Moreover, GRF1 and GRF3 transcript levels were reduced in 2-week-old ahk2 ahk3 double mutant plants, corroborating that GRFs and cytokinins interact (Liu et al, 2014b).…”
Section: Grf5 and Cytokinins As Coordinators Of Chloroplast Division mentioning
confidence: 85%
“…8). GRF1 is also involved in basal disease resistance by positively regulating TGA1 and TGA4 and negatively regulating TGA3 and TGA7 (Kesarwani et al 2007;Shearer et al 2012;Liu et al 2014). This feature further suggested that overexpression of SpmiR396a-5p increased transgenic plants susceptibility to P. nicotianae infection.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal perception impinges on the activity of MIR396 promoters leading to a gradual decline in mature miR396 levels and a concomitant increase of miR396 target expression during the normal course of PTI. MiR396 targets can regulate growth and stress responses2425262728, MIM396 plants grow and develop normally. This result is in agreement with the minor changes observed in the global transcriptome in non-pathogen challenged MIM396 plants.…”
mentioning
confidence: 99%